Well- Differentiated Osteosarcoma Of The Rib - Sameer Mohieldeen (College of Pharmacy / Mustansiriyah University, 2013)
Primary osteosarcoma are one of the most common malignant bone tumors principally affecting the long bones in children and adolescent. Well differentiated osteosarcoma of the rib is extremely rare, there is no sex. Predominance and the mean age is in the third decade. The tumor has strong predilection for the long bones of the extremities, especially the metaphysis but may occur in the diaphysis. Radiological, the lesion shows no distinctive features, often simulating fibrous dysplasia or desmoplastic fibroma. I report a case of well differentiated osteosarcoma involving the (7th,8th,9th,) left ribs of 25-year-old male. This is a peculiar case of well differentiated osteosarcoma involving an unusual site. This patient underwent a wide excision of the tumor of the ribs and the pleura and chest wall reconstruction. The patient followed by courses of chemotherapy, and follow up for 22-monthes with no sign of recurrence. Classic microscopic feature of a ramifying osteoid matrix amidst the tumor cells was diagnostic of an osteosarcoma